(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
في هذا العمل نقوم بتقدير ثابت هلدر للتحويل المحافظ الذي ينقل القرص الواحدي K إلى المضلع المحدب المغلق G الذي يملك n ضلع , توجد دراسة تثبت وجود هذا الثابت و تبين أن أس هلدر لهذا التحويل يعطى بالعدد حيث: الزوايا الداخلية للمضلع. In this study, we estimate Holder’s constant of conformable mapping which maps unitary disc into a convex polygon of n sides. There are some studies that prove the existence of this constant and explain the relationship between the Polygon angles and Holder’s index :.